DIABETES EXERCISE AS AN ALTERNATIVE TO PREVENT DIABETES MELLITUS IN ADOLESCENTS - Poppy Elisano Arfanda; Ians Aprilo; M. Adam Mappaompo; Muhammad Qasash Hasyim; Retno Farhana Nurulita (Bajang Institute, 2024)
Diabetes Mellitus (DM) has been an important problem, along with increasing obesity which is currently a cause of death. This service aims to create reliable pioneers in Diabetes Exercise (DE). These pioneers are provided with DE which can have direct implications in society. This DE is designed with 7 warm-up movements, 4 core movements, and 5 cool-down movements. Before carrying out the service, the subject is given material in the form of a video, then the service member takes a pretest score. After that, the teacher provides good and correct movement material to the subject by giving examples of each movement. Then the subjects were divided into small groups to learn diabetes exercise movements, at the end of the meeting a pretest score was taken to determine the subject's mastery of the movements. The final results showed that 41 subjects or 46.1% were in the good category